A-Level Chemistry - Ramsden, E. N. (United Kingdom Nelson Thornes, 2000)
This highly regarded textbook covers all the main A Level Chemistry specifications.
Include Index, Appendix, Table, Graph and Illustration
Keywords: Chemistry--Study and teaching -- Chemistry--Examinations -- A-level examinations